Program Edukasi Pencegahan Pelecehan Seksual untuk Mewujudkan Lingkungan Sekolah Menengah Kejuruan yang Aman dan Inklusif - Ariya Trisya; Nevalita Aulya Wibowo; Hasan Basri; Ana Fatmawati Angraini; Rosdiana Rosdiana (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Sexual harassment in school environments constitutes a violation of human dignity and is explicitly regulated under the Sexual Violence Crimes Law Undang-Undang Nomor 12 Tahun 2022 tentang Tindak Pidana Kekerasan Seksual (UU TPKS). This paper assesses a legal-education program’s effectiveness in enhancing students’ understanding of what constitutes sexual harassment, the significance of consent, and reporting mechanisms within the school context. Employing a community service method with interactive lectures, discussions, and case studies, combined with normative legal analysis of UU TPKS provisions, the study demonstrates a significant improvement in students’ awareness of both non-physical and physical forms of harassment, and their readiness to report incidents. The findings indicate that legal education in schools serves as a vital preventive and protective instrument to uphold victims’ rights and prevent sexual violence.